2020
DOI: 10.3390/dj8010017
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Biodentine™ ® with Periodontal Ligament Stem Cells: In Vitro Study

Abstract: Biodentine™ is a tricalcium silicate-based cement material that has a great impact on different biological processes of dental stem cells, compared to other biomaterials. Therefore, we aimed to investigate the optimum biocompatible concentration of Biodentine™ with stem cells derived from periodontal ligament (hPDLSCs) by determining cell proliferation, cytotoxicity, migration, adhesion and mineralization potential. hPDLSCs were treated with Biodentine™ extract at different concentrations; 20, 2, 0.2 and 0.02 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 42 publications
(56 reference statements)
5
16
0
Order By: Relevance
“…In this context, Abuarqoub et al . (2020), have shown recently that Biodentine, suspended as a powder in culture medium, exhibited cytotoxic effects at higher concentrations (20 mg mL −1 ) on human stem cells derived from periodontal ligament (hPDLSCs), whereas the concentrations lower than 2 mg mL −1 were noncytotoxic. Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Abuarqoub et al . (2020), have shown recently that Biodentine, suspended as a powder in culture medium, exhibited cytotoxic effects at higher concentrations (20 mg mL −1 ) on human stem cells derived from periodontal ligament (hPDLSCs), whereas the concentrations lower than 2 mg mL −1 were noncytotoxic. Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
“…2010, Abuarqoub et al . 2020). High basic pH is known to be extremely cytotoxic, and under such conditions, it is not possible to demonstrate the specific effects of Biodentine.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing BioC R, TF BCR and IR FS reported an adequate cytocompatibility of the tested materials, exhibiting similar results to a negative control group (Abuarqoub et al, 2020;Rodríguez-Lozano et al, 2020a). All of the aforementioned cements showed a high cell adhesion and morphology (Abuarqoub et al, 2020;Luo et al, 2018;Rodríguez-Lozano et al, 2020a). Additionally, BD, BioC R, TF BCR and IR FS-treated hPDLSCs exhibited an upregulation of one or more cementogenic, osteogenic and/or odontogenic markers (Abuarqoub et al, 2020 BCR also showed a significantly higher mineralization potential compared to a negative control (Rodríguez-Lozano et al, 2020a).…”
Section: Study Resultsmentioning
confidence: 58%
“…Amongst the 9 CSCs evaluated, BD was the only cement which exhibited significant positive results in cell viability and migration assays when compared to a negative control group (unconditioned culture medium; Abuarqoub et al, 2020). Studies assessing BioC R, TF BCR and IR FS reported an adequate cytocompatibility of the tested materials, exhibiting similar results to a negative control group (Abuarqoub et al, 2020;Rodríguez-Lozano et al, 2020a). All of the aforementioned cements showed a high cell adhesion and morphology (Abuarqoub et al, 2020;Luo et al, 2018;Rodríguez-Lozano et al, 2020a).…”
Section: Study Resultsmentioning
confidence: 88%
“…Likewise, 2 mg/ml Biodentine is the most biocompatible concentration to promote migration, attachment, and mineralization of human PDLSCs. Biodentine at low concentrations (2.00, 0.20 and 0.02 mg/ml) significantly enhances viability of human PDLSCs, while Biodentine at higher concentrations (20 mg/ml) exhibits cytotoxicity, which may be associated with high pH ( 104 ). High pH of Biodentine results in an increased concentration of iron and calcium ions in the extracellular environment ( 105 ).…”
Section: Stem Cellsmentioning
confidence: 99%